PERBEDAAN PROTEIN URINE IBU MUDA DENGAN LANSIA DI DESA KEDUNGPANDAN, KEC. JABON, SIDOARJO: THE DIFFERENCE OF URINE PROTEIN BETWEEN YOUNG MOTHER AND ELDERLY MOTHER IN KEDUNGPANDAN VILLAGE, JABON DISTRICTS, SIDOARJO - Santoso, Andreas Putro Ragil; Wulandari, Devyana Dyah (Stikes Wira Medika Bali, 2019)
The body's protein functions greatly in the metabolic process and will be utilized by the body, especially tissues in the process of bodily activities, but over time the body will experience changes in activity. As you age, more and more tissue will also be inactive. This study aims to determine whether there is a difference in urine protein of young mothers with the elderly in Kedungpandan village, Kec. Jabon, Sidoarjo. The study design used analytic observation with cross sectional approach. The study population was 38 and determined based on the Slovin formula determined 33 samples, namely 33 elderly samples and 33 samples of young mothers. The sampling technique is done using probability sampling techniques. The results of research conducted based on the Mann-Whitney test showed that p> 0.05 ie 0.379 showed that there was no difference between urine protein in young mothers and urine protein in the elderly in Kedungpandan village, Jabon district, Sidoarjo